Pedagogía de la fraternidad en situaciones de riesgo, formación integral para la vida (2012)
This article aims to contribute to the foundation of the pedagogy of fraternity in situations of risk, as a new vision of the pedagogy in which many elements of other theories are present, but which are taken from a different perspective, whose goal is to allow educational processes that make a fairer and more fraternal society possible, by generating friendship, trust, and reciprocal esteem, in the first place, that knowledge is always increased as a manner to solve the answers to the issues of society, in the second place, and in the third place, it can generate a space in which the family can be felt